A SnO2-H2Ti2O5 coaxial fiber and its preparation method and application

By adopting the SnO2-H2Ti2O5 coaxial fiber structure, the porosity of the H2Ti2O5 shell and the gap buffer volume expansion of the SnO2 core are solved, and the higher electrochemical lithium storage performance and service life are achieved.

CN115148973BActive Publication Date: 2025-02-14YIBIN VOCATIONAL & TECH COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210850583.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-19
Publication Date
2025-02-14
Estimated Expiration
2042-07-19

AI Technical Summary

Technical Problem

The existing SnO2 negative electrode material expands and shrinks during the circulating deliquification process, resulting in material powdering and rapid attenuation of battery capacity, poor cycle stability, and difficult to achieve practicality.

Method used

The SnO2-H2Ti2O5 coaxial fiber structure is adopted, where the H2Ti2O5 shell has a porous structure, a gap exists between the SnO2 core and the shell, and the volume expansion of SnO2 is buffered, and it is prepared by electrospinning and heat treatment.

Benefits of technology

It improves the cycle stability and electrochemical lithium storage performance of SnO2 negative electrode material, extends the service life of the battery, and reduces process complexity and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115148973B_ABST
    Figure CN115148973B_ABST
Patent Text Reader

Abstract

The present invention discloses a SnO2-H2Ti2O5 coaxial fiber and a preparation method and application thereof. In the SnO2-H2Ti2O5 coaxial fiber, SnO2 is used as a core axis, H2Ti2O5 is used as an outer shell, the diameter distribution of the inner axis is 100-200 nm, the diameter distribution of the outer axis is 300-500 nm, and the specific surface area is 100 m 2 g ‑1 ~300 m 2 g ‑1 The present invention combines electrospinning technology and room temperature alkaline heating method to form a core-shell coaxial structure in situ, breaking through the traditional secondary coating preparation method. The overall process is simple and has strong controllability. The SnO2-H2Ti2O5 coaxial fiber prepared by the present invention has a stable nano-scale multi-level structure, which can effectively alleviate the volume expansion effect during lithium insertion, has stable cyclic lithium storage performance, and can be used as a high-performance lithium-ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode materials for lithium-ion batteries, and in particular to a SnO2-H2Ti2O5 coaxial fiber and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the most popular electrochemical energy storage technology currently being studied and have been widely used in portable electronic devices, electric vehicles and other fields. Therefore, many scientific researchers are committed to developing lithium-ion batteries with high capacity and long service life to meet the growing demand for large-scale power supply and energy storage equipment. Among them, the performance of the negative electrode material largely determines the performance of the lithium-ion battery. The traditional negative electrode material of lithium-ion batteries is generally graphite, but its theoretical specific capacity is only 372 mA hg -1 , which is difficult to meet the current demand. The research and development of negative electrodes with high lithium storage capacity to replace graphite negative electrodes is a current research hotspot.

[0003] Tin-based oxides (such as SnO2) are anode materials due to their large lithium storage capacity (~ 800 mA h g -1 ) and a suitable charge and discharge platform voltage, it is considered to be a potential negative electrode that can replace graphite. However, during the cyclic insertion and extraction of lithium, the volume of the SnO2 negative electrode will repeatedly expand and shrink, which will cause the negative electrode material to pulverize and fall off the current collector, resulting in a significant attenuation of the battery capacity in a short period of time. Therefore, the practical application of SnO2 negative electrode materials has always been difficult to achieve due to its poor cycle stability. In order to overcome this shortcoming and promote the practical application of SnO2 negative electrode materials, researchers have compounded SnO2 with materials that have less volume expansion when inserted into lithium, and then with the help of nanostructured structure design, the negative impact of the volume expansion effect of SnO2 can be effectively alleviated. For example, depositing a layer of carbon material on the surface of SnO2 microspheres to form SnO2@C core-shell spheres can buffer the volume expansion of SnO2 to a certain extent and improve the cycle stability of the electrode. Other types of core-shell structures such as SnO2@C "yolk-shell" structure, SnO2@TiO2 coaxial fiber, SnO2@C coaxial fiber, etc. have been reported and also show relatively stable cyclic lithium storage stability.

[0004] However, previous material designs basically require a secondary coating method to achieve a core-shell structure, which is a complex process that takes a long time and consumes a lot of energy. It is difficult to directly construct a core-shell SnO2-based composite negative electrode material through in-situ chemical synthesis, and related work has been slow to progress.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] In order to solve the problems of difficulty in constructing SnO2 core-shell structure and poor cycle stability in the prior art, the present invention provides a novel SnO2-H2Ti2O5 coaxial fiber and a preparation method and application thereof.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A SnO2-H2Ti2O5 coaxial nanofiber, wherein the outer shell of the coaxial nanofiber is porous H2Ti2O5, the inner shaft is SnO2, the outer diameter of the coaxial nanofiber is 300-500 nm, the inner diameter is 100-200 nm, and there is a gap between the inner shaft and the outer shell. The specific surface area of ​​the coaxial nanofiber is 100-300 m 2 g -1 .

[0009] In addition, the present invention also provides a method for preparing the above SnO2-H2Ti2O5 coaxial fiber, comprising the following steps:

[0010] (1) Electrospinning: Titanium salt, tin salt, tetraethyl orthosilicate, and polyvinyl pyrrolidone are dissolved in ethanol to obtain a spinning solution, and then the composite fiber is prepared by electrospinning technology;

[0011] (2) Heat treatment: heat treating the composite fiber in step (1) in an air atmosphere to remove polyvinyl pyrrolidone and oxidize the titanium salt, tin salt and tetraethyl orthosilicate to obtain SnO2-TiO2-SiO2 fiber;

[0012] (3) Alkaline solution treatment: The SnO2-TiO2-SiO2 fiber prepared in step (2) is placed in an alkaline aqueous solution to dissolve SiO2 and promote the formation of the H2Ti2O5 shell, thereby obtaining SnO2-H2Ti2O5 coaxial fibers.

[0013] Preferably, the titanium salt described in step (1) is a mixture of one or more of tetrabutyl titanate, titanium isopropoxide, and titanium tetrachloride. Preferably, the tin salt described in step (1) is a mixture of one or more of stannous octoate, stannous acetate, and tin tetrachloride.

[0014] Preferably, in step (1), the amount of the tin salt is 0.5 to 3 mmol, the amount of the titanium salt is 1 to 4 mmol, the amount of the tetraethyl orthosilicate is 5 to 15 mmol, the amount of the polyvinyl pyrrolidone is 0.8 to 1.5 g, and the amount of the ethanol is 5 to 15 ml.

[0015] Preferably, the parameters of the electrostatic spray treatment in step (1) are: the electrostatic spray voltage is 10 to 18 kV; the liquid push rate is 0.1 to 1 ml h -1 .

[0016] Preferably, the temperature of the heat treatment in step (2) is 500°C to 800°C, the time of the heat treatment is 30 to 120 min, and the heating rate is 5 to 20°C / min.

[0017] Preferably, the alkali solution in step (3) is one or more of NaOH aqueous solution, ammonia water, and KOH aqueous solution.

[0018] Preferably, the concentration of the alkali solution in step (3) is 0.5 to 5 mol L -1 .

[0019] Preferably, the temperature of the alkali solution treatment in step (3) is 20°C, and the time of the insulation treatment is 3 to 72 hours.

[0020] The invention also provides the application of SnO2-H2Ti2O5 coaxial fiber in the negative electrode of lithium ion battery.

[0021] The SnO2-H2Ti2O5 coaxial fiber material of the present invention is made into a negative electrode of a lithium ion battery according to the following steps, and an electrochemical performance test is performed: the SnO2-H2Ti2O5 coaxial fiber material (80 wt%) and the conductive carbon black Super-P (10 wt%) are fully mixed by mortar grinding. Then polyvinylidene fluoride (10 wt%) and N-methylpyrrolidone 20 times the mass of polyvinylidene fluoride are added in sequence, and the mixture is fully stirred to form a slurry. The mixed slurry is evenly coated on the surface of the copper foil and placed in a vacuum drying oven at 110°C for vacuum drying for 12 hours. After taking it out, the copper foil is cut into a small disc negative electrode with a diameter of 12 mm by a cutting machine, and assembled into a button battery in a glove box for electrochemical performance testing.

[0022] The present invention has the following advantages: (1) the SnO2-H2Ti2O5 coaxial fiber structure is directly formed in situ by alkaline solution treatment, the process is simple and controllable, and the uniformity is good; (2) the outer shell H2Ti2O5 has a stable structure during lithium storage and almost no volume change, and can be used as a supporting structure to ensure the structural stability of the inner core SnO2; and the gap between the core and the shell can buffer the volume expansion of SnO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope photo of the SnO2-H2Ti2O5 coaxial fiber in Example 1 of the present invention, which is magnified 100,000 times;

[0024] Figure 2 This is a cycle performance diagram of a battery assembled with SnO2-H2Ti2O5 coaxial fibers in Example 1 of the present invention;

[0025] Figure 3 This is a cycle performance diagram of the battery assembled with SnO2-TiO2 coaxial fibers in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The SnO2-H2Ti2O5 coaxial fiber material prepared by the present invention is further described below in conjunction with the accompanying drawings and the preparation method of the present invention:

[0027] Example 1

[0028] The preparation method of SnO2-H2Ti2O5 coaxial fiber in this embodiment is as follows:

[0029] (1) Weigh 3 mmol of tetrabutyl titanate, 2 mmol of stannous octoate, 5 mmol of ethyl orthosilicate and 1 g of polyvinyl pyrrolidone and dissolve them in 10 ml of ethanol. Stir mechanically to obtain a homogeneous spinning solution. Then, composite fibers were prepared by electrospinning. The specific parameters of the electrospinning device were as follows: voltage: 12 kV; temperature: 20 °C; humidity: 50%; receiving distance: 15 cm; feeding speed: 0.5 ml h -1 ;

[0030] (2) placing the composite fiber in a muffle furnace for heat treatment at a heating rate of 10 °C / min, a heat treatment temperature of 500 °C, and a heat treatment time of 120 min, and obtaining SnO2-TiO2-SiO2 fiber after natural cooling;

[0031] (3) The SnO2-TiO2-SiO2 fiber was immersed in a 2 mol / L potassium hydroxide aqueous solution at 20 °C for 24 h to obtain SnO2-H2Ti2O5 coaxial fiber.

[0032] The SnO2-H2Ti2O5 coaxial fibers prepared in Example 1 were used as negative electrode materials for lithium-ion batteries and assembled into lithium-ion half-cells to test their electrochemical lithium storage performance. -1 During charge and discharge, the first charge capacity is 735 mA hg -1 After 40 cycles, the capacity retention rate was 68%.

[0033] Example 2

[0034] The preparation method of SnO2-H2Ti2O5 coaxial fiber in this embodiment is as follows:

[0035] (1) Weigh 1 mmol of tetrabutyl titanate, 1.5 mmol of stannous octoate, 10 mmol of ethyl orthosilicate and 1 g of polyvinyl pyrrolidone and dissolve them in 15 ml of ethanol. Stir mechanically to obtain a homogeneous spinning solution. Then, composite fibers were prepared by electrospinning. The specific parameters of the electrospinning device were as follows: voltage: 15 kV; temperature: 20 °C; humidity: 50%; receiving distance: 15 cm; feeding speed: 1 ml h -1 ;

[0036] (2) placing the composite fiber in a muffle furnace for heat treatment at a heating rate of 15 °C / min, a heat treatment temperature of 400 °C, and a heat treatment time of 120 min, and obtaining SnO2-TiO2-SiO2 fiber after natural cooling;

[0037] (3) The SnO2-TiO2-SiO2 fiber was immersed in a 2 mol / L sodium hydroxide aqueous solution at 20 °C for 24 h to obtain SnO2-H2Ti2O5 coaxial fiber.

[0038] The SnO2-H2Ti2O5 coaxial fibers prepared in Example 2 were used as negative electrode materials for lithium-ion batteries and assembled into lithium-ion half-cells to test their electrochemical lithium storage performance. -1 During charge and discharge, the first charge capacity is 845 mA hg -1 After 40 cycles, the capacity retention rate is 55%.

[0039] Example 3

[0040] The preparation method of SnO2-H2Ti2O5 coaxial fiber in this embodiment is as follows:

[0041] (1) Weigh 1 mmol of tetrabutyl titanate, 2 mmol of stannous octoate, 10 mmol of ethyl orthosilicate, and 1 g of polyvinyl pyrrolidone and dissolve them in 5 ml of ethanol. Stir mechanically to obtain a homogeneous spinning solution. Then, composite fibers were prepared by electrospinning. The specific parameters of the electrospinning device were as follows: voltage: 18 kV; temperature: 20 °C; humidity: 50%; receiving distance: 18 cm; feeding speed: 1 ml h -1 ;

[0042] (2) placing the composite fiber in a muffle furnace for heat treatment at a heating rate of 10 °C / min, a heat treatment temperature of 600 °C, and a heat treatment time of 120 min, and obtaining SnO2-TiO2-SiO2 fiber after natural cooling;

[0043] (3) The SnO2-TiO2-SiO2 fiber was immersed in a 4 mol / L ammonia solution at 20 °C for 72 h to obtain SnO2-H2Ti2O5 coaxial fiber.

[0044] The SnO2-H2Ti2O5 coaxial fibers prepared in Example 3 were used as negative electrode materials for lithium-ion batteries and assembled into lithium-ion half-cells to test their electrochemical lithium storage performance. -1 Under charge and discharge, the first charge capacity is 800 mA hg -1 After 50 cycles, the capacity retention rate is 45%.

[0045] Comparative Example 1

[0046] 2 mmol of stannous octoate and 1 g of polyvinyl pyrrolidone were weighed and dissolved in 10 ml of ethanol and mechanically stirred to obtain a homogeneous spinning solution. Then, composite fibers were prepared by electrospinning. The specific parameters of the electrospinning device were voltage: 15 kV; temperature: 20 °C; humidity: 50%; receiving distance: 15 cm; feeding speed: 1 ml h -1 ;

[0047] The composite fiber was placed in a muffle furnace for heat treatment at a heating rate of 10 °C / min, a heat treatment temperature of 500 °C, and a heat treatment time of 120 min. After natural cooling, SnO2 fiber was obtained.

[0048] The SnO2 fiber was immersed in tetrabutyl titanate / ethanol solution for about 24 h. Tetrabutyl titanate was slowly hydrolyzed and polymerized on the surface of the SnO2 fiber to form a TiO2 shell, thereby obtaining a SnO2-TiO2 coaxial fiber.

[0049] The SnO2-TiO2 coaxial fibers prepared in Comparative Example 1 were used as negative electrode materials for lithium-ion batteries and assembled into lithium-ion half-cells to test their electrochemical lithium storage performance. -1 During charge and discharge, the first charge capacity is 794mA hg -1 After 40 cycles, the capacity retention rate was 21%.

[0050] Compared with this method, the coaxial fiber negative electrode prepared by the method of the present invention has higher cycle stability. This is because the pores between the "core" and "shell" of the coaxial fiber in the method of the present application are large, which can accommodate the volume expansion of SnO2; while the pore space in the coaxial fiber prepared by the secondary coating method is small, and the volume expansion of SnO2 is difficult to suppress, so the cycle stability is poor. In addition, a uniform and controllable coaxial core-shell structure can be obtained based on the spinning-hydrothermal one-step treatment method, but the uniformity of the coaxial fiber structure obtained by the traditional secondary coating method is difficult to control.

[0051] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A SnO2-H2Ti2O5 coaxial nanofiber, characterized in that: The outer shell of the coaxial nanofiber is porous H2Ti2O5, the inner shaft is SnO2, the outer diameter of the coaxial nanofiber is 300-500 nm, the inner diameter is 100-200 nm, there is a gap between the inner shaft and the outer shell, and the specific surface area of ​​the coaxial nanofiber is 100-300 m 2 •g -1 .

2. A method for preparing SnO2-H2Ti2O5 coaxial nanofibers as claimed in claim 1, characterized in that: The following steps are involved: (1) Electrospinning: Titanium salt, tin salt, tetraethyl orthosilicate, and polyvinyl pyrrolidone are dissolved in ethanol to obtain a spinning solution, and then composite fibers are prepared by electrospinning; (2) Heat treatment: heat treating the composite fiber obtained in step (1) in an air atmosphere to remove polyvinyl pyrrolidone and oxidize the titanium salt, tin salt and tetraethyl orthosilicate to obtain SnO2-TiO2-SiO2 fiber; (3) Alkali solution treatment: The SnO2-TiO2-SiO2 fiber obtained in step (2) is treated in an alkaline solution to obtain SnO2-H2Ti2O5 coaxial fiber.

3. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2, characterized in that: The titanium salt is a mixture of one or more of tetrabutyl titanate, titanium isopropoxide, and titanium tetrachloride; the tin salt is a mixture of one or more of stannous octoate, stannous acetate, and tin tetrachloride.

4. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2 or 3, characterized in that: The amount of the titanium salt is 1 to 4 mmol, the amount of the tin salt is 0.5 to 2 mmol, the amount of the tetraethyl orthosilicate is 5 to 15 mmol, the amount of the polyvinyl pyrrolidone is 0.8 to 1.5 g, and the amount of the ethanol is 5 to 15 ml.

5. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2, characterized in that: The process parameters of the electrospinning in step (1) are: the electrostatic spray voltage is 10 to 18 kV; the liquid pushing rate is 0.1 to 1 ml •h -1 .

6. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2, characterized in that: The temperature of the heat treatment in step (2) is 500-800°C, the time of the heat treatment is 30-120 min, and the heating rate of the heat treatment is 5-20°C / min.

7. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2, characterized in that: The alkali solution in step (3) is one or more of NaOH aqueous solution, KOH aqueous solution, and ammonia water, and the concentration of the alkali solution is 0.5 to 5 mol•L -1 .

8. The method for preparing SnO2-H2Ti2O5 coaxial fiber according to claim 2, characterized in that: The temperature of the alkali solution treatment is 20° C., and the treatment time is 3 to 72 hours.

9. Use of the SnO2-H2Ti2O5 coaxial nanofibers according to claim 1 as negative electrode material in a negative electrode of a lithium ion battery.